Modeling River Water Levels in Tidal Swamp Areas using HEC–RAS to Determine the Hydrotopography of Tidal Farmland - Faiz Afnan Nurrahman; Chandra Setyawan; Hanggar Ganara Mawandha (The University of Lampung, 2025)
Swamp land is a natural resource that can be utilized to improve community welfare, because swamp land is one of the potential natural resources and can be used as agricultural land development. The aim of this research is to analyze the tidal water movement patterns of rivers and channels in the swamp irrigation area of Palingkau. The stages in this research included the installation of an Automatic Water Level Recorder (AWLR) to collect real-time water level data, then modeling the tidal movement of river water level using HEC–RAS modeling. The results of this research showed that the pattern of tidal water flow movement in the swamp irrigation area of Palingkau is diurnal tide, characterized by the existence of one high tide and one low tide in one day. Furthermore, HEC–RAS modeling can be used to describe the tide of water levels in the swamp irrigation area of Palingkau. Validation of the HEC–RAS model shows that the tidal flow modeling simulation is good and very suitable for use. Based on the hydrotopography class, the land at the research location is classified into 3 classes, namely hydrotopography classes of B, C, and D. Keywords: Agriculture, HEC–RAS Modeling, Hydrotopography, Land, Swamp.